2018
DOI: 10.3390/geosciences8060214
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interpretation of Marine Sedimentary Environments Using Multi-Frequency Multibeam Backscatter Data

Abstract: Backscatter mosaics based on a multi-frequency multibeam echosounder survey in the continental shelf setting of the North Sea were compared. The uncalibrated backscatter data were recorded with frequencies of 200, 400 and 600 kHz. The results showed that the seafloor appears mostly featureless in acoustic backscatter mosaics derived from 600 kHz data. The same area surveyed with 200 kHz reveals numerous backscatter anomalies with diameters of 10-70 m deviating between −2 dB and +4 dB from the background sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…Although we did not use a multibeam echosounder with multispectral mode (such as the R2Sonic 2026) for our measurements, we repeated the hydroacoustic surveys with different frequencies. Similar research has been presented in [62], where the surveys were repeated with three different frequencies: 200, 400, and 600 kHz. This approach helped us to make a detailed acoustic characterization of the seabed sediments.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although we did not use a multibeam echosounder with multispectral mode (such as the R2Sonic 2026) for our measurements, we repeated the hydroacoustic surveys with different frequencies. Similar research has been presented in [62], where the surveys were repeated with three different frequencies: 200, 400, and 600 kHz. This approach helped us to make a detailed acoustic characterization of the seabed sediments.…”
Section: Discussionmentioning
confidence: 76%
“…Multi-frequency, multibeam echosounder data is a promising new approach in the characterization of seabed habitats. Recent research confirms that the simultaneous analysis of many frequencies leads to a better understanding of seafloor properties [62]. Although we did not use a multibeam echosounder with multispectral mode (such as the R2Sonic 2026) for our measurements, we repeated the hydroacoustic surveys with different frequencies.…”
Section: Discussionmentioning
confidence: 96%
“…It indicates that the bottom detection, the high BS level and the unusual angular response at 90 kHz for muddy sediments results from scattering at subsurface structures. 17 17 . Figure 12 shows modeled ARCs at frequencies of 90 and 450 kHz for a layered medium with different layer thicknesses and sediment properties using the layered BS model (Section 3.2 and Table 2). As a reference, the ARCs of the first and second layer assuming a non-layered model are additionally displayed.…”
Section: Time Series Signalmentioning
confidence: 99%
“…Recent research studies employing multispectral BS data have shown improvements in sediment and habitat mapping. The acquisition of multispectral BS data has been achieved by using either different acoustic sensors (i.e., MBES and Side-scan sonar) [15], various MBESs [16], or a single broadband MBES running multiple track lines [17]. New developments in marine sonar technology allow the MBES to collect spatially and temporally co-located BS data at multiple frequencies (i.e., 90 to 450 kHz) using a single system.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable direct classification of cobbles and fine boulders will need higher resolution input data, which can be difficult for large areas of interest. If covering a large percentage of seafloor, the presence of cobbles and fine boulders may be detected indirectly, e.g., by utilizing angular response curves [35,36] and multifrequency backscatter approaches currently under active development [37][38][39][40]. Eventually, the density of medium and large boulders may be used as a proxy for the overall density of hard substrata available for biota and consequently for the identification of reefs sensu habitats directive (code 1170).…”
Section: Constraining the Minimum Size Of Detected Bouldersmentioning
confidence: 99%